2022
DOI: 10.1097/j.jcrs.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of refractive and visual outcomes of 3 presbyopia-correcting intraocular lenses

Abstract: The new Synergy IOL showed better DCVAs for close vergence demands compared with PanOptix and POD F IOLs and better UIVA compared with the POD F trifocal IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 31 publications
(85 reference statements)
6
46
1
1
Order By: Relevance
“…A previous clinical study demonstrated that these results were consistent with the results of the present study. Earlier studies have reported monocular UDVAs of 0.13 ± 0.13 6 for ZXR00 and 0.04 ± 0.10 12,30 for ZFR00. Earlier studies have reported monocular CDVA of 0.05 ± 0.08 6 and 0.01 ± 0.02 25 for ZXR00 and −0.02 ± 0.07 12 and −0.04 ± 0.02 25 for ZFR00.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A previous clinical study demonstrated that these results were consistent with the results of the present study. Earlier studies have reported monocular UDVAs of 0.13 ± 0.13 6 for ZXR00 and 0.04 ± 0.10 12,30 for ZFR00. Earlier studies have reported monocular CDVA of 0.05 ± 0.08 6 and 0.01 ± 0.02 25 for ZXR00 and −0.02 ± 0.07 12 and −0.04 ± 0.02 25 for ZFR00.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study with ZFR00 IOL, it was reported that over 50% of patients experienced night halos, 12 however, the very annoying halo or glare rate was less than that of PanOptix ® (Alcon aboratories, Inc., Fort Worth, TX, USA) or FineVision ® POD F (PhysIOL SA, Liège, Belgium). 30 Some of the patients who had the ZFR00 IOL inserted complained of decreased UDVA, but the actual UDVA and CDVA were like those of the ZXR00 group. The discomfort associated with optical quality may be expressed as a decrease in the distance vision.…”
Section: Discussionmentioning
confidence: 92%
“…A newly introduced ZFR00 has been designed to blend the diffractive factors of multifocal IOL (Tecnis ® Multifocal, Johnson & Johnson Vision, Santa Ana, CA, USA) and EDOF (Tecnis Symfony ® , Johnson & Johnson Vision, Santa Ana, CA, USA) IOL [6]. The manufacturers say that the hybrid optical technology in ZFR00 aims to combine the good distant and near visual acuity scores of a diffractive multifocal IOL with a continuous vision from far to near vision performance of an EDOF IOL [9]. As of December 2021, five papers on ZFR00 have been published.…”
Section: Discussionmentioning
confidence: 99%
“…As of December 2021, five papers on ZFR00 have been published. Three articles reported only the clinical findings of ZFR00 and one study comparing the IOL to Acrysof IQ ® Panoptix IOL (Alcon Laboratories, Inc., Fort Worth, Texas, USA) and FineVision ® POD F IOL (PhysIOL, Liège, Belgium) [7][8][9]. The other is a comparison of the outcomes of six types of presbyopia-correcting IOLs [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation